2020
DOI: 10.3389/fmicb.2020.596422
|View full text |Cite
|
Sign up to set email alerts
|

Marek’s Disease Virus (Gallid alphaherpesvirus 2)-Encoded miR-M2-5p Simultaneously Promotes Cell Proliferation and Suppresses Apoptosis Through RBM24 and MYOD1-Mediated Signaling Pathways

Abstract: MicroRNAs (miRNAs) have been demonstrated for their involvement in virus biology and pathogenesis, including functioning as key determinants of virally-induced cancers. As an important oncogenic α-herpesvirus affecting poultry health, Marek's disease virus serotype 1 [Gallid alphaherpesvirus 2 (GaHV-2)] induces rapid-onset T-cell lymphomatous disease commonly referred to as Marek's disease (MD), an excellent biological model for the study of virally-induced cancer in the natural hosts. Previously, we have demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…A good example is Marek's disease virus (MDV), which has evolved from a relatively harmless paralytic syndrome into a highly virulent pathogen [153][154][155]. Marek's disease is caused by oncogenic Gallid alphaherpesvirus 2 (GaHV-2), commonly known as MDV type 1 (MDV-1) [154,156,157]. This disease is characteristic for young chickens, but older birds can also be affected.…”
Section: Trichosporon Asahiimentioning
confidence: 99%
“…A good example is Marek's disease virus (MDV), which has evolved from a relatively harmless paralytic syndrome into a highly virulent pathogen [153][154][155]. Marek's disease is caused by oncogenic Gallid alphaherpesvirus 2 (GaHV-2), commonly known as MDV type 1 (MDV-1) [154,156,157]. This disease is characteristic for young chickens, but older birds can also be affected.…”
Section: Trichosporon Asahiimentioning
confidence: 99%
“…It was reported that MDV1-miR-M3 suppressed cisplatin-induced apoptosis by targeting SMAD2, a critical component in the transforming growth factor (TGF) β signal pathway, thus creating a cellular environment favorable to virus replication ( 111 ). Similarly, virus-encoded miR-M2-5p promotes cell viability and inhibits cell apoptosis through RBM24 and MYOD1-mediated signaling pathways ( 112 ). It seems that MDV modulates host response by self-encoded miRNAs targeting cellular proteins to favor viral survival and replication during viral infection.…”
Section: Innate Immune Evasion By Marek’s Disease Virus (Mdv)mentioning
confidence: 99%